Bilateral Ethmoidal Mucocele Causing Proptosis in a Child. Issue 4 (June 2021) - Sen, Comert; Aydemir, Levent; Comoglu, Senol; Sonmez, Said; Ozturk, Ilker Erdinc; Deger, Kemal
Abstract : Objectives: Paranasal sinus mucocele is a benign cystic lesion, lined with respiratory epithelium and filled with mucoid secretions, which is generally seen in the ethmoid or frontal sinuses. Inflammation, trauma, fibrosis, neoplasm, and previous surgery play a role in etiology. Treatment of this condition requires marsupialization and drainage. Endoscopic surgery is the gold standard procedure. Methods: A 2-year-old boy was referred to our clinic with a diagnosis of bilateral ethmoid mucocele causing proptosis in the right eye. General clinical examinations and routine blood analysis revealed normal health condition of the patient and comorbidities such as cystic fibrosis (CF) and/or ciliary dysfunction were excluded. The patient was operated with an endoscopic endonasal approach. Results: As far as we know, our article reports the first case of bilateral ethmoidal sinus mucocele with no underlying comorbidity, such as cystic fibrosis or ciliary dyskinesia. Conclusions: Children are rarely affected by mucocele and if present at early age, there is usually an underlying cause. In pediatric patients with signs and symptoms suggestive of a mucocele, it is important to rule out other benign and malignant paranasal sinus pathologies. Marsupialization and drainage via endoscopic endonasal approach is the preferred treatment modality.